ADVANCE CARE PLANNING WHO, WHEN AND WHERE. WHAT IS THE EVIDANCE TO SUPPORT THE CALL TO PLAN EARLY. Issue 2 (1st June 2013) - Sands, M B; Norris, C; Varndel, W; Caplan, G
Abstract : Background: Eighty-six per cent of Australians state a preference to die peacefully at home, in fact only around 20% die at home. What is the evidence that supports our approach to Advance Care Planning? What populations can be effectively targeted? What are the necessary components that comprise and accompany an effective ACP? What are the barriers? What are the important outcomes? How do we provide confidence in the availability of care outside the acute setting to permit the ideal of staff and families/carers following an ACP and avoiding crisis transfers? What is the role of the acute setting in ACP? Aim: To review the evidence that supports a co-ordianated approach to ACP. Methods: This presentation is a systematic review of the evidence that informs our approach to ACP in primary and secondary health care settings Results: The evidence to support a comprehensive, tailored approach to identifying patients who might benefit from ACP, an approach to symptom management and carer support in a primary health care setting with appropriate co-ordination with specialist palliative care will be presented. Discussion: Only 4% of decedents do not have an the Emergency Department (ED) Presentation in the last year of life. The trajectory of chronic illness and co-morbidity determine that ED presentations provide the opportunity to identify patients who might benefit from ACP how can this inform our approach? Conclusion: Advance Care Planning has been associated with improved patient outcomes. The suggested approach supports the aspiration to Plan EARLY, and identifies appropriate target populations and outcome measures.